2017
DOI: 10.1002/slct.201701328
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide‐Bridged Mixed‐Valence Tetranuclear Cobalt 4‐Nitrophenol Inclusion Complex Showing Single Molecule Magnet Property

Abstract: Two tetranuclear hydroxide‐bridged mixed‐valence cobalt complexes, one having 4‐nitrophenolate anions and other having 4‐nitrophenol as guest, namely [(μ2‐dea)2(phen)2Co2(μ3‐OH)2Co2(phen)2](np)4•H2O (1), [(μ2‐dea)2(phen)2Co2(μ3‐OH)2 Co2(phen)2]Cl4•2Hnp•9H2O (2) (Hnp=4‐nitrophenol, phen=1,10‐phenanthroline, dea=di‐deprotonated diethanolamine) were synthesized and structurally characterized. Complex cation of these two complexes are based on Co4O4(OH)2 units where two cobalt ions are in Co2+ and other two are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The temperature dependence of χT (χ is the magnetic susceptibility, equal to M / H per two Co II ions) was studied on 1 in the temperature range of 2–300 K at 2500 Oe (Figure ). At 300 K, the measured χT value is 4.5 cm 3 mol –1 K, which lies in the expected range for two HS d 7 Co II ions ( S = 2 × 3/2, g = 2.0; χT = 2 × 1.875 cm 3 mol –1 K) (contribution from one pseudo-octahedral and another tetrahedral Co­(II) coordination polyhedron). The χT value decreases gradually with a decrease in the temperature to reach a value of 4.1 cm 3 mol –1 K at 50 K and then decreases abruptly, reaching a minimum of 2.6 cm 3 mol –1 K at 2 K. In addition, Co­(II) complexes in a similar type of Co­(N3) 2 coordination environment exhibit spin crossover behavior depending on the appropriate ligand field. However, for complex 1 , we have not observed any such property in the measured temperature range from 2 to 300 K, which is also confirmed by DSC measurements (Figure S30).…”
Section: Results and Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The temperature dependence of χT (χ is the magnetic susceptibility, equal to M / H per two Co II ions) was studied on 1 in the temperature range of 2–300 K at 2500 Oe (Figure ). At 300 K, the measured χT value is 4.5 cm 3 mol –1 K, which lies in the expected range for two HS d 7 Co II ions ( S = 2 × 3/2, g = 2.0; χT = 2 × 1.875 cm 3 mol –1 K) (contribution from one pseudo-octahedral and another tetrahedral Co­(II) coordination polyhedron). The χT value decreases gradually with a decrease in the temperature to reach a value of 4.1 cm 3 mol –1 K at 50 K and then decreases abruptly, reaching a minimum of 2.6 cm 3 mol –1 K at 2 K. In addition, Co­(II) complexes in a similar type of Co­(N3) 2 coordination environment exhibit spin crossover behavior depending on the appropriate ligand field. However, for complex 1 , we have not observed any such property in the measured temperature range from 2 to 300 K, which is also confirmed by DSC measurements (Figure S30).…”
Section: Results and Discussionmentioning
confidence: 56%
“…The magnetic properties of 2 were investigated by measuring the temperature dependence of χT in the temperature range of 2.5–280 K at 1000 Oe (Figure ). The measured χT value at 280 K is 2.57 cm 3 mol –1 K, which is significantly larger than the spin-only value for one HS d 7 Co II ion ( S = 3/2, g = 2.0; χT = 1.875 cm 3 mol –1 K), indicating the presence of an orbital angular momentum contribution. Upon a decrease in the temperature, the χT value decreases slowly to reach a value of 2.39 cm 3 mol –1 K at 100 K. On a further decrease in temperature, the χT value decreases abruptly to a value of 1.68 cm 3 mol –1 K at 2.5 K. DSC measurements confirm the absence of phase transition at the measured temperature range from 295 to 130 K (Figure S31) and thus the absence of spin crossover properties.…”
Section: Results and Discussionmentioning
confidence: 89%
“…Compared with this work, their structures had the same coordinated environment of cobalt [23], and in 2017, Baruah's group reported the other butterfly-type structure when we compared with our work. In Baruah's work, all Co(II) ions have six-coordinative environments in all structures [17].…”
Section: Crystal Structurementioning
confidence: 96%
“…Under direct-current field of 0.1 T, the energy hills and extrapolated relaxation time were U eff = 28.36 K and τ 0 = 1.5 × 10 −10 s for 1 (Figure 6c), U eff = 21.11 K and τ 0 = 3.0 × 10 −8 s for 2 ( Figure 6d). Compared with the magnetic properties of the same type of structure, it is found that the work has the highest energy hill under the condition of applied magnetic field [17,23]. The Cole-Cole plots (Figures 6a,b and S5) were generated from the ac-susceptibilities using a generalized Debye model.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation